2018
DOI: 10.1007/s00442-018-4240-1
|View full text |Cite
|
Sign up to set email alerts
|

Do grazers respond to or control food quality? Cross-scale analysis of algivorous fish in littoral Lake Tanganyika

Abstract: Food quality determines the growth rate of primary consumers and ecosystem trophic efficiencies, but it is not clear whether variation in primary consumer densities control, or is controlled by, variation in food quality. We quantified variation in the density and condition of an abundant algae-eating cichlid, Tropheus brichardi, with respect to the quality and productivity of algal biofilms within and across rocky coastal sites in Lake Tanganyika, East Africa. Adjacent land use and sediment deposition in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…For example, as was noted above, extreme weather events and watershed deforestation are increasing sediment loading to littoral habitats (Hambright et al 2004 ). In tropical Lake Tanganyika, sediments compromised the growth and feeding activity of algivorous fish, leading to a positive correlation between sediments and attached algal biomass (Munubi et al 2018 ). In addition to directly (Wagenhoff et al 2013 ) and indirectly (Munubi et al 2018 ) promoting filamentous algal growth, sediments fill interstitial spaces, reducing total habitat and promoting hypoxia in sediments.…”
Section: Hypothesis 3: Shifting Biotic Interactions Can Favor Filamentous Algaementioning
confidence: 99%
See 1 more Smart Citation
“…For example, as was noted above, extreme weather events and watershed deforestation are increasing sediment loading to littoral habitats (Hambright et al 2004 ). In tropical Lake Tanganyika, sediments compromised the growth and feeding activity of algivorous fish, leading to a positive correlation between sediments and attached algal biomass (Munubi et al 2018 ). In addition to directly (Wagenhoff et al 2013 ) and indirectly (Munubi et al 2018 ) promoting filamentous algal growth, sediments fill interstitial spaces, reducing total habitat and promoting hypoxia in sediments.…”
Section: Hypothesis 3: Shifting Biotic Interactions Can Favor Filamentous Algaementioning
confidence: 99%
“…In tropical Lake Tanganyika, sediments compromised the growth and feeding activity of algivorous fish, leading to a positive correlation between sediments and attached algal biomass (Munubi et al 2018 ). In addition to directly (Wagenhoff et al 2013 ) and indirectly (Munubi et al 2018 ) promoting filamentous algal growth, sediments fill interstitial spaces, reducing total habitat and promoting hypoxia in sediments. Filamentous algal proliferations themselves can create adverse environmental conditions for zoobenthos (Arroyo et al 2012 ).…”
Section: Hypothesis 3: Shifting Biotic Interactions Can Favor Filamentous Algaementioning
confidence: 99%
“…Our experiment with T. gracilentus, in conjunction with a model fit to the experimental data, gave evidence that midges do not inherently overexploit their resources. Consumers often employ behaviors that mitigate the likelihood of overexploitation of their resources (Vuorinen et al 2021), such as enhancing resource growth rates through ecosystem engineering (Jones et al 1994) and abandoning low-resource habitat patches (Power 1984, Wiley and Warren 1992, Munubi et al 2018, both of which we observed by T. gracilentus. How consumers manage their resources in a dynamic environment may shape their somatic growth rates and subsequently their population dynamics.…”
Section: Discussionmentioning
confidence: 71%
“…In addition to depressing biomass, grazing increases nutrient turnover [27]. Because benthic consumers track primary producer availability, their grazing can result in uniformly low algal biomass even across strong contrasts in environmental productivity [28,29], particularly for the benthic algal groups that are preferentially grazed. However, compared to phytoplankton communities (which are dispersed throughout the euphotic zone), benthic biofilms are a spatially concentrated food.…”
Section: Cryptic Grazing In Benthic Food Websmentioning
confidence: 99%